Physiological potential and initial development of soybean plants as a function of seed treatment - Del Bem Junior, Luciano [UNESP]; Ferrari, Jonas Leandro [UNESP]; Dario, Gustavo [UNESP]; Triboni, Yago de Barros [UNESP]; Raetano, Carlos Gilberto [UNESP] (Univ Federal Goias, 2019)
Seed treatment is a process that helps to control insects and soil-borne pathogens, besides allowing a given crop to reach its maximum production potential and protect its seedlings. This study aimed to evaluate the physiological performance of seeds and the initial development of soybean, as a function of seed treatment. The study was based on a completely randomized design, with five treatments [imidacloprid + thiodicarb (75 + 225 g a. i. 100 kg(-1) of seeds); chlorantraniliprole (62.5 g a. i. 100 kg(-1) of seeds); cyantraniliprole (72 g a. i. 100 kg(-1) of seeds), fipronil + thiophanate-methyl + pyraclostrobin (5 + 45 + 50 g a. i. 100 kg(-1) of seeds); and control (seeds without treatment)]. Initially, the physiological quality of the seeds was evaluated by determining the first germination count, final germination and accelerated aging, with four replications. After that, the effect of the seed treatment on the soybean plant development was evaluated by analyzing the leaf area, number of leaves, shoot height, root and shoot dry mass and fresh mass of root nodules, with ten replications. The seed treatment with fipronil + pyraclostrobin + thiophanate-methyl allows an increased germination when the seeds are subjected to the accelerated aging test, besides an increment in the shoot height and leaf area of the plants.
Keywords: Glycine max; germination; seed accelerated aging